2018
DOI: 10.3390/molecules23081925
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-High Performance Liquid Chromatography with Tandem Mass Spectrometry Method for Determination of 10 Alkaloids in Beagle Dog Plasma after the Oral Administration of the Corydalis yanhusuo W.T. Wang Extract and Yuanhuzhitong Tablets

Abstract: This study has developed a sensitive and simple ultra-high performance liquid chromatography-electrospray ionization-tandem mass spectrometry method for the simultaneous determination of corydaline, dehydrocorydaline, tetrahydropalmatine, protopine, palmatine, tetrahydroberberine, columbamine, berberine, coptisine and berberrubine in beagle dog plasma after the oral administration of the Corydalis yanhusuo W.T. Wang and Yuanhuzhitong tablets. Chromatographic separation was achieved on an Agilent Eclipse Plus C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The retro‐Diels–Alder (RDA) reaction is a characteristic fragmentation pathway of tetrahydroprotoberberine alkaloids 18,21,22 . As an example, corydaline was identified by comparison of the retention time and MS/MS data of the corresponding standard and previous literature 23,24 . The proposed RDA pathway is shown in Figure 3B .…”
Section: Resultsmentioning
confidence: 99%
“…The retro‐Diels–Alder (RDA) reaction is a characteristic fragmentation pathway of tetrahydroprotoberberine alkaloids 18,21,22 . As an example, corydaline was identified by comparison of the retention time and MS/MS data of the corresponding standard and previous literature 23,24 . The proposed RDA pathway is shown in Figure 3B .…”
Section: Resultsmentioning
confidence: 99%
“…According to the theory of TCM processing, the toxicity of drugs is reduced and the effects of moving Qi and relieving pain are enhanced by stirfrying with vinegar. Modern research showed that the seven free alkaloid compounds such as protopine, palmatine chloride, berberine, dehydrocorydaline, tetrahydropalmatine, tetrahydroberberine, and corydaline [3][4][5][6][7][8][9] in CR are the main active and characteristic components, which are often used to evaluate the quality of CR. Modern pharmacological studies have indicated that the alkaloid compounds in CR have sedative, analgesic, antitumor, and other pharmacological effects [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As a classical CPM, this formulation has been commonly used for treating all kinds of pains, such as headache, gastralgia, dysmenorrhea, and costalgia (Li et al, 2018;Wang et al, 2019). YHS is the main constituent herb in YHZT, and according to previous pharmacological studies, alkaloids have been proven to be the major bioactive ingredients in YHS (Cui et al, 2018;Guo et al, 2019;Zhang et al, 2016). For instance, tetrahydropalmatine (THP) is a crucial alkaloid isolated from YHS (Ou et al, 2006) and has been selected as a quantitative marker for quality control of both YHS and YHZT in the ChP 2020 Edition Volume I (Chinese Pharmacopoeia Commission, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies demonstrated that two enantiomers usually behave differently in terms of pharmacodynamic and pharmacokinetic properties (Campo, Bernardes, & Carvalho, 2009;Zhang et al, 2012), but studies on ChP or other studies of quality analysis were generally performed on racemic THP (Cui et al, 2018;Ping et al, 2019).…”
Section: Introductionmentioning
confidence: 99%